Oncostatin M suppresses browning of white adipocytes via gp130-STAT3 signaling - Pim P. van Krieken; Timothy S. Odermatt; Marcela Borsigova; Matthias Blüher; Stephan Wueest; Daniel Konrad (Elsevier, 2021)
Objective: Obesity is associated with low-grade adipose tissue inflammation and locally elevated levels of several glycoprotein 130 (gp130) cytokines. The conversion of white into brown-like adipocytes (browning) may increase energy expenditure and revert the positive energy balance that underlies obesity. Although different gp130 cytokines and their downstream targets were shown to regulate expression of the key browning marker uncoupling protein 1 (Ucp1), it remains largely unknown how this contributes to the development and maintenance of obesity. Herein, we aim to study the role of gp130 cytokine signaling in white adipose tissue (WAT) browning in the obese state. Methods: Protein and gene expression levels of UCP1 and other thermogenic markers were assessed in a subcutaneous adipocyte cell line, adipose tissue depots from control or adipocyte-specific gp130 knockout (gp130Δadipo) mice fed either chow or a high-fat diet (HFD), or subcutaneous WAT biopsies from a human cohort of lean and obese subjects. WAT browning was modeled in vitro by exposing mature adipocytes to isoproterenol after stimulation with gp130 cytokines. ERK and JAK-STAT signaling were blocked using the inhibitors U0126 and Tofacitinib, respectively. Results: Inguinal WAT of HFD-fed gp130Δadipo mice exhibited significantly elevated levels of UCP1 and other browning markers such as Cidea and Pgc-1α. In vitro, treatment with the gp130 cytokine oncostatin M (OSM) lowered isoproterenol-induced UCP1 protein and gene expression levels in a dose-dependent manner. Mechanistically, OSM mediated the inhibition of Ucp1 via the JAK-STAT but not the ERK pathway. As with mouse data, OSM gene expression in human WAT positively correlated with BMI (r = 0.284, p = 0.021, n = 66) and negatively with UCP1 expression (r = −0.413, p < 0.001, n = 66). Conclusions: Our data support the notion that OSM negatively regulates thermogenesis in WAT and thus may be an attractive target for treating obesity.